Family violence in the United States: defining, understanding, and combating abuse - Hines, Denise A. (SAGE, 2021)
"Attention is paid to larger social systems that can contribute to abuse, as well as community, relationship, and individual predictors of both perpetration and victimization. Additionally, there is an emphasis on both prevention and intervention of family violence at various levels of the ecological model. Authors Denise A. Hines, Kathleen Malley-Morrison, and Leila B. Dutton help students explore what family violence is and the reasons why it happens. Their approach covers contemporary and controversial topics across the lifespan, including maltreatment of male partners by women, of parents, within sexual minority relationships, and on college campuses. This 3rd edition is filled with chapter-opening cases to prompt discussion within the classroom as well as considerations of context and application in the larger community. Rich in scholarly references and case materials, it is suitable for advanced undergraduates, graduate students, and professionals alike"--